Will the new legal framework within the EU prevent another crisis? Undirtitill: Directive on Recovery and Resolution of credit institutions and investment firms; BRRD - Sigurveig Guðmundsdóttir 1971- (2017)
The Great recession is as the name indicates, the largest recession in history to date and the one most widely spread. The answer of the EU and US authorities to the Great recession has been transformation of financial regulations, both in the US and Europe. One of the legislative measures is the European Union's Directive on Recovery and resolution of credit institutions and investment firms (BRRD). The purpose of the Directive is to provide the authorities, the flexibility to intervene much sooner by setting in place recovery plans and intervention powers before resorting to serious measures like a bail-out, a bail-in or winding-up the financial institution. The purpose of the Directive is furthermore intended to ensure that the dissolution is handled in a similar manner everywhere within Europe. I will look to the substance of articles and books discussing the directive and the financial crisis, in Iceland, the EU and the U.S., and what various experts consider to be best to prevent or reduce the harmful effect a financial crisis can have. It seems that most experts conclude that the required capital banks hold is too small and many of them address the flaws of the RWA methodology and the complexity of the capital requirement. Also that there are still ways for the Member States to avoid bail-in and revert to bail-out. Some of the resolution measures covered by the BRRD directive are quite similar to the measures applied in resolution of the three failed banks in Iceland in 2008-2010. I will compare the Directive to the “Icelandic way” as far as it can be compared. How effective is the new BRRD? Will it be sufficient to solve the problem caused in last crises? In short, in case of dealing with many banks or institutions in distress, one cannot expect the measures in the BRRD to be sufficient. Even in 2017, many major banks are still too interconnected to fail. It seems that the Directive is too complicated and that simpler methodology could be applied.